Pelatihan Penggunaan Canva dan PosSaku untuk Meningkatkan Kreativitas dan Produktivitas UMKM - Fitriana, Nur; Hairani, Afni Putri; Julfandi, Julfandi; Pauziah, Sarah Nur; Murniati, Sri; Putri, Suci Yolanda; Fitra, Subhanul (LPPI UMN AL WASHLIYAH, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in national economic development, yet they still face major challenges, particularly in graphic design creativity and manual financial recordkeeping. Digitalization has become an urgent need to enable MSMEs to remain competitive amid the era of technological transformation. To address this need, a community service program was carried out in the form of training on the use of Canva and PosSaku application for MSME actors in the Food Court Nusantara area, Mal SKA. The aim of this activity was to improve participants’ understanding and skills in designing digital promotional brochures using Canva, as well as managing financial records more efficiently through the PosSaku application. The training method was participatory and interactive, consisting of material delivery, independent practice, mentoring, and evaluation of participants’ work. The results of the training showed a significant improvement in the participants’ skills, which included business owners and employees of a fried chicken (ayam geprek) business. All participants were able to independently create promotional brochures using Canva and gained an understanding of the importance of visual branding in business. Moreover, the use of PosSaku enabled participants to record sales and expenses in real-time, prepare simple financial reports, and make business decisions based on actual data. This training successfully raised participants’ awareness of the importance of technology for business sustainability and development, and served as an initial step toward broader digital transformation for MSMEs.